IN THE STUDY OF ENGLISH - THE QUESTION OF LANGUAGE AND CULTURE HARMONY. - Maftuna Khotamova Xoliqul qizi , (TADQIQOTLAR.UZ, 2023)
Annotation: This article delves into the significance of harmony in the study of the English language and culture. It explores the interconnectedness of language and culture, and how understanding and fostering harmony between them can enhance intercultural communication. The article combines literature analysis, a discussion of methods, and presents results from various studies. It concludes by discussing the implications and offering suggestions for future research and practical applications.